The impact of social responsibility in achieving the philosophy of clean production - an applied study of the opinions of a sample of employees in the Iraqi General Cement Company - علاء فرحان طالب; امير غانم العوادي (Iraqi Journal for Administrative Sciences, 2024)
Impact social responsibility in achieving cleaner production philosophy The clean production processes are contemporary methods adopted by organizations that aim to improve the reality of production and environmental sustainability through the approach of social responsibility and employment dimensions to achieve a clean production philosophy and achieve a competitive advantage unique to all competitors. The study relied on two approaches, deductive as input variables of the study to test and try to apply them to the respondent to gain access to the data and then the results of society. The analytical test to measure the variables of the study through an examination and analysis of the results and then test the variables of the study. The study dealt with some intellectual and field problems and the goal of answering them to clarify theoretical philosophy and intellectual connotations and applied fields of variables (social responsibility, clean production) covered by the study. In addition to the statement of the importance of these variables and the possibility of their application in the Iraqi environment, specifically in the cement industry and in particular in the company researched " Iraqi Cement State Company" The study sample included a group of technicians and managers of departments where. Totaling 132 people were distributed the questionnaire as a tool to gather information The study found there is a significance positive correlation between the variables of the study with a significant positive correlation differences between the dimensions of the study variables (the dimensions of social responsibility, and clean production processes) also found the presence of clear impact of social responsibility dimensions to clean production directly And the study it urged the company researched to give a clean production philosophy greater importance than ever before . Because it the key to current and future competitive advantage because of the increased pressure for the sustainability of the environment and consumer protection.